Do nocturnal headaches matter? A prospective diary study on subjective sleep parameters in snorers and their bed partners. (June 2014) - Seidel, Stefan; Frantal, Sophie; Salhofer-Polanyi, Sabine; Lieba-Samal, Doris; Zeitlhofer, Josef; Wöber, Christian
Background: The objective of this study was to assess the influence of nocturnal headaches (NH) on subjective sleep parameters prospectively in habitual snorers and their bed partners. Methods: We recruited habitual snorers and their bed partners via newspaper articles. The participants completed a semistructured interview, filled in questionnaires about quality of sleep (PSQI), daytime sleepiness (ESS), depression (SDS) and anxiety (SAS) and they kept a 90-day headache and sleep diary. Results: Seventy-six snorers (25 female) and 41 bed partners (31 female) completed the study recording a total of 6690 and 3497 diary days, respectively. NH were recorded on 222 (3.3%) and 79 (2.2%) days in 32 (42%) snorers and 17 (41%) bed partners, respectively. Snorers with NH showed significantly higher PSQI (5 ± 3 vs. 4 ± 2, p  = 0.004), SAS (38 ± 11 vs. 31 ± 10, p  = 0.011) and SDS scores (39 ± 12 vs. 34 ± 10, p  = 0.048) than snorers without NH. For bed partners with NH we found a significant female predominance (sex ratio f:m = 16:1 vs. 12:12, p  = 0.005) and significantly higher SAS scores (38 ± 6 vs. 33 ± 8, p  = 0.030) compared with bed partners without NH. The subjective quality of sleep in habitual snorers ( p  < 0.001) as well as their bed partners ( p  = 0.017) was negatively influenced by NH, but not total sleep time. Discussion: NH occurred in around 40% of snorers and their bed partners at least once during the 90-day observation period. Our results confirmed a negative impact on the subjective quality of sleep in both groups.